2005
DOI: 10.1007/s00270-004-0208-0
|View full text |Cite
|
Sign up to set email alerts
|

Radiofrequency Ablation Therapy Combined with Cementoplasty for Painful Bone Metastases: Initial Experience

Abstract: The purpose of this study was to assess the efficacy and safety of percutaneous radiofrequency (RF) ablation therapy combined with cementoplasty under computed tomography and fluoroscopic guidance for painful bone metastases. Seventeen adult patients with 23 painful bone metastases underwent RF ablation therapy combined with cementoplasty during a 2-year period. The mean tumor size was 52 x 40 x 59 mm. Initial pain relief, reduction of analgesics, duration of pain relief, recurrence rate of pain, survival rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
82
0
10

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(93 citation statements)
references
References 8 publications
1
82
0
10
Order By: Relevance
“…In the above-mentioned series (8,9), osteoplasty was shown to be safe and effective in the treatment of painful bone metastases refractory to conventional therapy and with no surgical options. Although the complication rate was very low, subsequent recurrence of fractures in long bones suggested that the treatment was inadequate in those cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the above-mentioned series (8,9), osteoplasty was shown to be safe and effective in the treatment of painful bone metastases refractory to conventional therapy and with no surgical options. Although the complication rate was very low, subsequent recurrence of fractures in long bones suggested that the treatment was inadequate in those cases.…”
Section: Discussionmentioning
confidence: 99%
“…In such cases, percutaneous osteoplasty (also called cementoplasty) could be performed for stabilization of the fracture. This procedure was previously described (8,9), but results were discouraging because a high rate of delayed fractures of the treated bone shaft was reported. Previously, a case of a pathologic fracture of the humeral shaft was treated by percutaneous osteoplasty with use of a bone cement-filled catheter resulting in pain relief (10).…”
mentioning
confidence: 99%
“…Desde el punto de vista clínico, los resultados son buenos con mejoría del dolor en las primeras 24 horas en todos los pacientes, resultados similares a los obtenidos por otros autores (8)(9)(10)(11)(12)(13). En lo relativo a los aspectos técnicos, la combinación de ambas técnicas no incrementa la complejidad del procedimiento ya que el acceso transpedicular empleado, para la realización de la cifoplastia, es el mismo que se requiere para la realización de la RF previa, con la excepción de que el acceso óseo inicial para efectuar la ablación se realizó con agujas de 11G, que posteriormente se intercambian por el sistema de acceso de cifoplastia.…”
Section: Figunclassified
“…Estudios recientes sugieren que los tratamientos percutáneos, mínimamente invasivos, pueden contribuir al manejo de estos pacientes (3,4,(6)(7)(8)(9)(10)(11)(12)(13).…”
Section: Introductionunclassified
“…Concerning pain reduction, the combination of thermal ablation and vertebroplasty shows high success rates, which can be up to 100 % [3]. In general, there are two different thermal ablation methods: radiofrequency ablation (RFA) and radiofrequency ionization (coblation).…”
Section: Introductionmentioning
confidence: 99%